Adaptation of an exercise intervention for pregnant women to community-based delivery: a study protocol - Aline Andres; Elisabet Børsheim; Taren Swindle; Audrey Martinez (BMJ Open)
Introduction Despite well-established guidelines and benefits to exercise, the majority of pregnant women in the USA fail to meet recommended activity levels. Studies need to determine feasible ways to translate clinical interventions to community settings by engaging pregnant women in widely accessible locations to ensure benefits to more women. The aim of this study is to adapt and determine feasibility, acceptability and fidelity of the research clinic-based Expecting intervention (NCT02125149) with pregnant women with obesity in community settings.Methods and analysis We will use the Replicating Effective Programs (REP) to guide the adaptation and implementation of the research clinic-based intervention into the community. REP provides a four-phase process for implementing evidence-based interventions including collection of feedback from community stakeholders, iterative piloting of the intervention in the community and a process for standardising the intervention across community settings. Following adaptation, the updated intervention will be piloted. The pilot study will include 60 expecting women. We will randomise half to receive the community-adapted Expecting intervention (intervention, N=30) and half to receive standard of care (control, N=30). Feasibility and Acceptability of Intervention Measures are primary outcomes as key indicators of feasibility. Secondary outcomes will include the number of intervention sessions completed, the change in the number of minutes of physical activity as measured by accelerometer, as well as change in health indicators from enrolment to time of delivery and 6 months post-delivery (ie, body mass index, blood pressure and total cholesterol).Ethics and dissemination This study has been approved by the Institutional Review Board (#260132). Findings will be shared with study participants and stakeholder advisors through written summaries and in-person presentations; results will also be shared through presentations at scientific conferences and publications in peer-reviewed journals.Trial registration number NCT04298125; Pre-results.